The Determinants of E-Disclosure Attitude: Empirical Evidences from Italian and Spanish Municipalities. Issue 11 (18th August 2018) - Gesuele, Benedetta; Metallo, Concetta; Longobardi, Sergio
ABSTRACT: Research investigates the attitude to the information disclosure via website, analysing a sample of 287 Italian and Spanish municipalities. A Tobit regression approach is adopted to explore the main determinants of e-disclosure. The findings show that municipality's factors like Internet visibility, wealth and leverage play an important role to determine the level of e-disclosure. In addition, a cluster analysis highlights that in Italy there is a greater level of e-disclosure than in Spain, revealing a set of specific elements that characterize municipalities with higher disclosure.